Vitamin D and the immunomodulation of rotator cuff injury - Dougherty KA; Dilisio MF; Agrawal DK (Dove Medical Press, 2016)
Kaitlin A Dougherty,1 Matthew F Dilisio,2 Devendra K Agrawal1 1Department of Clinical & Translational Science, 2Department of Orthopedic Surgery, Creighton University School of Medicine, Omaha, NE, USA Abstract: Tendon-to-bone healing after rotator cuff repair surgery has a failure rate of 20%–94%. There has been a recent interest to determine the factors that act as determinants between successful and unsuccessful rotator cuff repair. Vitamin D level in patients is one of the factors that have been linked to bone and muscle proliferation and healing, and it may have an effect on tendon-to-bone healing. The purpose of this article is to critically review relevant published research that relates to the effect of vitamin D on rotator cuff tears and subsequent healing. A review of the literature was conducted to identify all studies that investigate the relationship between vitamin D and tendon healing, in addition to its mechanism of action. The data were then analyzed in order to summarize what is currently known about vitamin D, rotator cuff pathology, and tendon-to-bone healing. The activated metabolite of vitamin D, 1α,25-dihydroxyvitamin D3, affects osteoblast proliferation and differentiation. Likewise, vitamin D plays a significant role in the tendon-to-bone healing process by increasing the bone mineral density and strengthening the skeletal muscles. The 1α,25-dihydroxyvitamin D3 binds to vitamin D receptors on myocytes to stimulate growth and proliferation. The form of vitamin D produced by the liver, calcifediol, is a key initiator of the myocyte healing process by moving phosphate into myocytes, which improves function and metabolism. Investigation into the effect of vitamin D on tendons has been sparse, but limited studies have been promising. Matrix metalloproteinases play an active role in remodeling the extracellular matrix (ECM) of tendons, particularly deleterious remodeling of the collagen fibers. Also, the levels of transforming growth factor-β3 positively influence the success of the surgery for rotator cuff repair. In the tendon-to-bone healing process, vitamin D has been shown to successfully influence bone and muscle healing, but more research is needed to delve into the mechanisms of vitamin D as a factor in skeletal tendon health and healing. Keywords: bone, calcium, 1,25-dihydroxyvitamin D, matrix metalloproteinases, muscle, rotator cuff tear, tendon